2011
DOI: 10.1021/ja204287n
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ni(II) in Reactions of SmI2: Sm(II)- or Ni(0)-Based Chemistry?

Abstract: The addition of catalytic amounts of Ni(II) salts provide enhanced reactivity and selectivity in numerous reactions of SmI(2), but the mechanistic basis for their effect is unknown. We report spectroscopic and kinetic studies on the mechanistic role of catalytic Ni(II) in the samarium Barbier reaction. The mechanistic studies presented herein show that the samarium Barbier reaction containing catalytic amounts of Ni(II) salts is driven solely by the reduction of Ni(II) to Ni(0) in a rate-limiting step. Once fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Nickel nanoparticles (NiNPs) were purchased from Sun Innovations (Fremont, CA) and have been previously characterized [15,56]. They are characterized as spherical in shape with a ~20 nm diameter, having a specific surface area of 40–60 m 2 /g, a metal purity of 99.9%, and insoluble in water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel nanoparticles (NiNPs) were purchased from Sun Innovations (Fremont, CA) and have been previously characterized [15,56]. They are characterized as spherical in shape with a ~20 nm diameter, having a specific surface area of 40–60 m 2 /g, a metal purity of 99.9%, and insoluble in water.…”
Section: Methodsmentioning
confidence: 99%
“…Size and shape have previously been verified by measuring digitized TEM images with Adobe Photoshop and determining pixel length of >100 NiNPs [15]. Furthermore, the oxidation state of these NiNPs is oxidation state (0) zero [56]. Prior to exposure, NiNPs were suspended in a sterile, 0.1% pluronic F-68 (Sigma) in phosphate buffered saline solution and dispersed for two hours using a bath sonicator at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Transition-metal salts, most commonly Ni II are used in place of HMPAi ns ome reactions including Barbier-type cross-coupling reactions, but it has been demonstrated that SmI 2 reducesN i II to Ni 0 which acts as the active coupling reagent. [5] The most widely used proton donors are water,m ethanol, and glycols and it is recognized that more hindered alcoholsd on ot form strong ground state complexes with Sm II . [6] Proton donors and Lewis bases that coordinate to SmI 2 may affect reactions through severald ifferentp athways.…”
Section: Introductionmentioning
confidence: 99%
“…Infra-Red (FT-IR) spectroscopy (Blackmond, 2005), ultraviolet-visible (UV/VIS) spectroscopy (Choquette et al, 2011), or nuclear magnetic resonance (NMR) spectroscopy (Mathew et al, 2006) to directly determine the concentration of the reaction components over the course of the reaction. These techniques are expensive and require a level of training which by far surpasses the level of first year undergraduate students.…”
Section: Introductionmentioning
confidence: 99%